Raton Businessman reaches out to Russia - Fleck, John (Albuquerque, NM Albuquerque Journal, 1994)
This article is about Larry Stolarczyk and his company working with the former Soviet Union's weaponeers in making non-military ventures as part of a newly formed United States Industry Coalition.
Newspaper article
Master list item #: 16
File location is in the Raton file Cabinet
Keywords: Stolarczyk, Larry -- Businessman; Domenici, Pete -- Senator; Ogloblin, Boris -- Russian Scientist; Hnatio, John -- Senator aide; Thompson, James -- UNM Dean of Engineering; United States Industry Coalition; Russian-U.S. Topaz International Program; U.S. University researchers; U.S. Departmetn of Energy; Sandia Labs; Los Alamos Labs; University of New Mexico University Center Research Park; U.S.-to-Russia Telecommunications; Non-Military Ventures; Technology; Local Business; Capitalism; Research Pojects; Engineering; Raton, New Mexico